2022
DOI: 10.1093/ofid/ofac214
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Assessment of Contact Tracing Operations for Coronavirus Disease 2019 in Pirkanmaa Hospital District, Finland

Abstract: Background The COVID-19 epidemic overwhelmed local contact tracing (CT) efforts in many countries. In Finland, SARS-Cov-2 incidence and mortality were among the lowest in Europe during 2020-2021. We evaluated CT efficiency, effectiveness, and transmission settings. Methods PCR test-positive COVID-19 cases and high-risk contacts in the population-based CT database of Pirkanmaa Hospital District (pop. 540,000) during June 2020–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Of these 6,113 COVID-19 cases, 21% had a known COVID-19 contact at work, but we don't know if the work-related exposure was with a patient, a colleague or some other contact at work, which has been shown to be sources for work-related infection [ 4 , 22 , 23 ]. In contact tracing data from Finland, it was reported that in healthcare settings most COVID-19 transmission took place between colleagues (62%) or from COVID-19 patients before their identification (33%) [ 24 ]. Only in 5% of the cases transmission occurred from a known COVID-19 patient.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 6,113 COVID-19 cases, 21% had a known COVID-19 contact at work, but we don't know if the work-related exposure was with a patient, a colleague or some other contact at work, which has been shown to be sources for work-related infection [ 4 , 22 , 23 ]. In contact tracing data from Finland, it was reported that in healthcare settings most COVID-19 transmission took place between colleagues (62%) or from COVID-19 patients before their identification (33%) [ 24 ]. Only in 5% of the cases transmission occurred from a known COVID-19 patient.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, everyone with respiratory symptoms was advised to be tested with SARS‐CoV NAAT free of charge. More specific testing criteria during the study period were previously described 9 . All venous thromboembolic events of the study patients (ICD‐10 diagnosis codes I26.0, I26.9, I80.0, I80.1, I80.2, I80.29, I80.3, I80.8, I80.9, I82.88 and I82.9) recorded 3 months after the test date in the Tampere University Hospital discharge records were identified.…”
Section: Vte Pe Group Group Size N N % N %mentioning
confidence: 99%
“…More specific testing criteria during the study period were previously described. 9 All venous thromboembolic events of the study patients (ICD-10 diagnosis codes I26.0, I26.9, I80.0, I80.1, I80.2, I80.29, I80.3, I80.8, I80.9, I82.88 and I82.9) recorded 3 months after the test date in the Tampere University Hospital discharge records were identified. Incidences of VTE and pulmonary embolism (PE) were calculated for the whole study population and for persons with positive and negative SARS-CoV-2 test results separately.…”
mentioning
confidence: 99%